Is the proximal adductor canal block a better choice than the distal adductor canal block for primary total knee arthroplasty?: A meta-analysis of randomized controlled trials. Issue 43 (23rd October 2020) - Zhang, Lu-kai; Chen, Cheng; Du, Wei-bin; Zhou, Hua-ten; Quan, Ren-fu; Liu, Jun-sheng
Abstract: Background: Total knee arthroplasty is accompanied by moderate to severe postoperative pain. Postoperative pain hampers the functional recovery and lowers patient satisfaction with the surgery. Recently, the adductor canal block (ACB) has been widely used in total knee arthroplasty. However, there is no definite answer as to the location of a continuous block within the ACBs. Method: Randomized controlled trials about relevant studies were searched in PubMed (1996 to Oct 2019), Embase (1996 to Oct 2019), and Cochrane Library (CENTRAL, Oct 2019). Results: Five studies involving 348 patients met the inclusion criteria. Pooled data indicated that the proximal ACB was as effective as the distal ACB in terms of total opioid consumption ( P = .54), average visual analog scale (VAS) score ( P = .35), worst VAS score ( P = .19), block success rate ( P = .86), and time of catheter insertion ( P = .54). Conclusions: Compared with the distal ACB, the proximal ACB showed similar analgesic efficacy for total opioid consumption, average VAS score, worst VAS score, block success rate, and time of catheter insertion. However, because of the limited number of involved studies, more high-quality studies are needed to further identify the optimal location of the ACB.